Evaluation of surface roughness and vertical shear reinforcement in contact zone of reinforced concrete constructions with survival moulds: /Gelžbetoninių konstrukcijų su liktiniais klojiniais jungiamojo strypyno ir betono paviršiaus šiurkštumo įvertinimas kontakto zonoje - Bistrickaitė, Rėda (Journal of Civil Engineering and Management, 2000)
Structurally and technologically expedient and economic precast-monolithic reinforcement floor slabs are widely used in western European countries. In Lithuania they are unknown, although there are all conditions for introducing them. Precast-monolithic slabs are made from precast layers (used as survival moulds) and monolithic layers (poured in situ). These layers are connected to make a compact structure with vertical shear reinforcement. There exists a method for calculating slabs analogous to a curved top truss. According to this method, the deflection of composite slabs increases considerably compared with that of one-layer structures. By evaluating both the transformation of tangential shear stress in the cross-section of bending elements and the influence of adhesive power in the contact zone, we have defined in a more exact way the method for calculating composite slabs. Additionally, we have included a vertical reinforcement into the structure and diminished vertical deflections of slabs up to the values close to those of one-layer structures. Article in Lithuanian. First Published Online: 26 Jul 2012